Vidya Kharishma PELATIHAN TEKNIK ECOPRINT UNTUK GURU PAUD - Vidya Kharishma; Ulfa Septiana (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2020)
One of early childhood education that can help children to convey ideas and imagination is art. Eco-print is atechnique of art that utilizes natural materials as its ingredients. It has the potential to be a teaching materialin early childhood education so children can appreciate and learns environmentally friendly art by harness thenatural material around them. However, an eco-print lesson in early childhood education is still scarce due tothe lack of teaching materials and the lack of the teacher’s knowledge, specifically about eco-print techniquesfor early childhood education. This problem initiates the author to design training and teaching materials abouteco-print techniques for teachers of early childhood education. Before the training conduct, there will beresearch preparation, analysis of participant needs, trial and error design of the eco print. After then, evaluationconduct between trainer and participant. Based on an analysis of participant needs, the best eco-printtechnique for this training is hammering, which is the most straightforward eco-print technique. However, thehammering technique, which usually uses a hammer, is replaced with pestle wood because it is safer forchildren. The implementation of training was carried successfully in the South Jakarta through the POSDAYAcommunity. The result shows that teachers can accept the teaching materials due to the nature of its easyimplementation, easily obtained material, and safety procedures.